Study on gamma-irradiation degradation of chitosan swollen in H₂O₂ solution and its antimicrobial activityfor E. coli - Dang , Xuan Du; Bui , Phuoc Phuc; Tran , Thi Thuy; Le , Anh Quoc; Dang , Van Phu; Nguyen , Quoc Hien (Nuclear Science and Technology, 2013)
Degradation of chitosan in swollen state with hydrogen peroxide solution (5% w/v) by γ- irradiation was investigated. Molecular weight (Mw) of irradiated chitosan was determined by gel permeation chromatography (GPC). Fourier transform infrared (FT-IR) and ultraviolet-visible (UVvis) spectrawere analyzed to study the structure changes of degraded chitosan. The results showed that the chitosan of low Mw ~30-45 kDawas efficiently prepared by γ-irradiation of chitosan swollen in hydrogen peroxide solution at low dose less than 20kGy. The main structure as well as the degree of deacetylation of the degraded chitosan was almost no significant change. Furthermore, the radiation degradation yield (Gs) was remarkably enhanced by the presence of H2O2. The obtained low Mw chitosan revealed high antimicrobial activity for E. colithat can be used for food preservation and other purposes as well.